Factors that affect the management of scientific research projects - Rosario Villarreal, Marco Aurelio (2019)
This research study aims to explain how there are external factors that directly influence the management of scientific and technological research projects financed with resources from the socioeconomic development fund of Camisea (Focam) of the National University of Huancavelica (UNH). Within these external factors that directly affect are the professional competencies of the research faculty and the logistic management that allows for the implementation of the research projects. A quantitative approach is used for this explanatory substantive research and the research design is non-experimental, cross-sectional, explanatory and causal. The sample included 49 engineering research profesors. For the present investigation, the survey technique was used for the three study variables. Findings - It can be affirmed that there is a positive influence of the professional competences and the logistic management on the management of the scientific research projects financed with resources of Focam of the UNH. This is the first research study that offers a discussion on the level of management of the scientific research projects carried out at the National University of Huancavelica, from research planning to the publication of the scientific article in an indexed journal. Alternative solutions are proposed for researchers and the logistics office to help efficiently manage scientific research projects.